(untitled) (Baghdad Science Journal, 2025)
Enterotoxin of Vibrio cholerae was extracted by cooling centrifuge at 6.000 rpm for 30 minntes. and filtrated by using milipore filter (0.22 ?m). The effect of crude enterotoxin on phagocytosis was studied by measuring the phagocytic index for 20 blood sample which were collected from healthy people and treated with enterotoxin in addition to control samples. From the results we found that phagocytic index of blood sample which were treated with enterotoxin was 42.9% while the phagocytic index of control blood samples was 64%. This means that there is a negative effect for the enterotoxin resulted from vibrio choleaa on the activity of phagocytic index.